Hubungan Paparan Tungau Debu Rumah dengan Riwayat Rinitis Alergi pada Anak di Salah Satu Panti Asuhan Kecamatan Pauh Kota Padang - Rahmat Agusman; Selfi Renita Rusjdi; Ade Asyari; Muhammad Rafif Sulthan Habibi; Ade Nofendra; Eryati Darwin; Eka Nofita (LPPM Institut Pendidikan Nusantara Global, 2026)
Allergic rhinitis is an inflammation of the nasal mucosa caused by a type I hypersensitivity reaction, which house dust mites (HDM) as one of the inhalant allergens causing allergic rhinitis. Children living in crowded environments, such as orphanages, are at high risk of HDM exposure. This study aimed to determine the relationship between house dust mite exposure and history of allergic rhinitis in children at an orphanage in Pauh District, Padang City.This was an observational analytical study with a cross-sectional approach. It was conducted at an orphanage in Pauh District, Padang City, and in the Parasitology Laboratory of the Faculty of Medicine, Andalas University, from March to August 2025. The sampling technique used was total sampling. Bed dust was collected using a vacuum cleaner, and interviews using the ISAAC questionnaire were conducted. Chi-square test was used to analyze the relationship between the two variables. The results of this study showed that all dust samples (100%) were positive, and the identification revealed that the most common species of house dust mites found was Dermatophagoides sp. (34,%), followed by Acarus sp. (19,14%), Cheyletus sp. (14,89%), Carpoglyphus sp. (10,63%) Glycyphagus sp. (8,51%), Thyrophagus sp. (8,51%), and Blomia tropicalis (4,25%). Most of the house dust mite density is in the low category with the average house dust mite density being 72,85 mites/gram of dust. The prevalence of allergic rhinitis in children based on the ISAAC questionnaire was 18.75%, with the highest prevalence in the 13–18 year age group. This study there was no significant association between house dust mite density and the history of allergic rhinitis. The conclusion of this study is that factors such as genetic predisposition, environmental conditions, and immune sensitization status are likely to contribute to the development of allergic rhinitis.